Analisis Geometri Akuifer Dangkal Mengunakan Metode Seismik Bias Reciprocal Hawkins (Studi Kasus Endapan Alluvial Daerah Sioux Park, Rapid Creek, South Dakota, United State of America) - Listiyani, Fenti; Yulianto, Gatot (BERKALA FISIKA, 2007)
Data processing of refraction Seismic with reciprocal Hawkins method have been done by using the secondary data in area of Sioux Park, Rapid Creek, South Dakota, United State of America which  has geology structure of alluvial sediment. The sediment Alluvial has the form of water carrier rock precipitated by Rapid Creek. The result of this research are: first layer with velocity vary from 268 m/s to 347 m/s consist of clay  functioning as covering layer, the second layer have velocities 939 m/s-1829 m/s, depth 0.28 m-3.43 m and thickness 0.26 m-4.40 m, lapped  over from clay, sand, and gravel functioning as carrier coat irrigate or coated acquifer and the third layer, have velocity 1874 m/s-2216 m/s lapped over from stone napal, acts as waterproof coat (impermeable). These acquifers are unconfined aquifer. Keywords: acquifer,  seismic refraction, ground water